2022
DOI: 10.33448/rsd-v11i14.35600
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Postural Corrective Training (TCP®) on overall glycemic control in diabetic middle-aged women

Abstract: Introduction: Diabetes mellitus (DM) is a disease manifested by chronic hyperglycemia resulting from changes in the secretion and / or action of insulin, which can cause tissue damage. The practice of physical exercise is often recommended in the treatment of this disease because it improves glucose uptake due to increased insulin sensitivity. Objective: to evaluate the effect of Corrective Postural Training (TCP®) on the glycemic metabolism of patients with type 2 diabetes. Methods: Twenty-one women between 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…One study measured the HBA1c levels of some middle-aged women that were involved in postural corrective exercise for about 20 weeks with a significant HBA1c reduction [33]. Another study showed that exercise and diet reduced blood glucose significantly and found out that there were cellular and molecular mechanism responsible for the effect of exercise on target organs leading to blood glucose reduction, in line with this study design and results [34]. In a study by Yang et al, a new hormone Irisin was discovered to be responsible for the conversion of the white fat to brown fat which can be metabolized and can only be secreted during exercise, and this was in line with the result in this study [35].…”
Section: Discussionsupporting
confidence: 65%
“…One study measured the HBA1c levels of some middle-aged women that were involved in postural corrective exercise for about 20 weeks with a significant HBA1c reduction [33]. Another study showed that exercise and diet reduced blood glucose significantly and found out that there were cellular and molecular mechanism responsible for the effect of exercise on target organs leading to blood glucose reduction, in line with this study design and results [34]. In a study by Yang et al, a new hormone Irisin was discovered to be responsible for the conversion of the white fat to brown fat which can be metabolized and can only be secreted during exercise, and this was in line with the result in this study [35].…”
Section: Discussionsupporting
confidence: 65%
“…Although the treatment of TB in the world through the Directly Observed Treatment Short course (DOTs) is either free or heavily subsidized, but the treatment of DM is not subsidized and in developing countries with poor health care facilities, controlling blood glucose with insulin in TB patients will be an uphill task [6]. The patients pay out-of-pocket due to poor health care financing where only five percent of the population has health insurance cover [12]. Although insulin is the preferred drug for achieving strict blood glucose control, it is expensive or unavailable especially in the low resource communities [6].…”
Section: Introductionmentioning
confidence: 99%